Synthesis and characterization of colloidal solution silver nanoparticles effect on behavioural changes and LC50 value of fish Cyprinus Carpio (linnaeus) - DR. CHIKKAPPA UDAGANI,; DR. SHIVARAJ YALLAPPA, (International Journal of Pharma and Bio Sciences, 2019)
Fish serves as a major source of healthy food owing to its higher protein, beneficial fat and various micro nutrients. Being healthy food for human, there should be a strong concern about the toxic effect of silver nanoparticles on fish. The objective of the present work is to study the effect of AgNPs on fish. The colloidal solution of AgNPs is prepared via chemical reduction method. The initial concentration of the AgNPs colloidal solution is estimated by the TEM micrograph and is found to be 317nm and the UV-visible spectrum of AgNPs is recorded using the Eppendorf BioSpectrometer kinetic for characterization. The freshwater fish, common carp, Cyprinus carpio exposed to lethal concentration of silver nanoparticles synthesized via chemical reduction method for a period of 4 days exposure. In this time, the obtained value of LC50 of AgNPs was 200ul/L. For the static renewal of exposure, the lethal concentration of silver nanoparticles were 50ul/L, 100ul/L, 150ul/L & 200ul/L including control group. Some of the behavioural symptoms/signs of the fish, behavioural changes like; swimming, restlessness, surfacing and hyper activity etc were observed at the time of exposure periods. This present work seems to be useful in analysing not only the disadvantages of using AgNPs but also their problems which arises different levels endpoints of the study and related to their use and these AgNPs is slightly toxic to all the organisms on this planet